Reusing Waste Bottles as Water Filters - Devi Sekar Palupi; Seris Mona; Nesa Sogya Tywula; Aprilla Sari; Silvia Fransisca (Indonesian Journal of Multidisciplinary Science, 2022)
Clean water is essential for everyone in both household needs and the business world. Health management or world health organization is needed to get clear water. The objective of this technique application is to provide a valuable lesson that can be used in the community to address clean water issues. From the practice of using used bottles as clean water filters, the water that was initially cloudy turned into clear, odorless water. It is because the materials used are coral, stone, gravel, sand, palm fiber, and charcoal.